Online Graduate Study of Health Care Learners' Perceptions of Instructional Immediacy - Melrose, Sherri; Bergeron, Kim (International Review of Research in Open and Distributed Learning, 2006)
Instructional immediacy is an established communication strategy that teachers can implement to create engaging learning environments. And yet, little is known about experiences distance education learners in graduate study programs have had with immediacy. This article presents findings from a qualitative research project designed to explore health care students' ideas about and activities related to instructional immediacy behaviors within a masters program offered exclusively through a WebCT online environment. A constructivist theoretical perspective and an action research approach framed the study. Data sources included two focus groups and ten individual audio-tape recorded transcribed interviews. Content was analyzed by both the primary researcher and an assistant for themes and confirmed through ongoing member checking with participants. The following three overarching themes were identified and are used to explain and describe significant features of instructional immediacy behaviors that health care learners who graduated from either a Master of Nursing or Master of Health Studies distance education program found valuable. 1) Model engaging and personal ways of connecting; 2) Maintain collegial relationships; and 3) Honor individual learning accomplishments.